Safety and effectiveness of telerehabilitation program in people with severe haemophilia in Chile. A qualitative study. (August 2022) - Aliaga-Castillo, Verónica; Horment-Lara, Giselle; Contreras-Sepúlveda, Felipe; Cruz-Montecinos, Carlos
Abstract: Introduction: Little is known about how people with haemophilia (PWH) perceive and assess the usefulness, safety and effectiveness of telerehabilitation. Objective : To describe usefulness, safety, effectiveness and limitations of a telerehabilitation program applied in people with severe haemophilia implemented during the COVID-19 pandemic in Chile. Design and Methods: A qualitative study was conducted based on a focus group. Four analytical categories were predefined, three of which involved elements of Donabedian's model for quality assessment in health care (structure, process and results). Results: One of the most important aspects according to all of the participants is the sense of safety they experienced while being taken care of by a physiotherapist specializing in PWH rehabilitation. This facilitated trust in the professional and adherence to treatment. All participants reported improvements in their physical condition and sense of well-being. The lack of adequate equipment at home, the limited length of the sessions, the perception that the physiotherapist may not be able to perform an appropriate physical examination and the lack of direct supervision were described as disadvantages. Conclusions: The findings underscored that telerehabilitation had high satisfaction among PWH. Telerehabilitation was perceived by PWH as a safe and effective intervention to improve physical condition. Telerehabilitation could be further supported and improved, and coverage could be enhanced, including rural and remote areas, which suffer from chronic inequalities in access to rehabilitation. The lack of face-to-face supervision and physical examination were perceived as the principal disadvantages. These results may help to improve telerehabilitation programs in PWH elsewhere. Highlights: Telerehabilitation had high satisfaction among PWH. Telerehabilitation was perceived by PWH as a safe and effective intervention. Telerehabilitation could improve coverage to rural and remote areas. The lack of face-to-face supervision was the main disadvantage.